Penerapan Metode Multi Factor Evaluation Process Pada Sistem Pendukung Keputusan Penentuan Kelayakan Pemberi Pinjaman (Studi Kasus NSC Finance Kota Lubuklinggau) - Andoko Andoko; Alfiarini Alfiarini; Robi Yanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
PT. Nusa Surya Ciptadana (NSC) Finance is a company engaged in the formal retail of motorcycles, which provides one of the services of credit fund lenders. As one of the companies that provide credit fund lending services, NSC Finance faced the problem that is in determining the feasibility of the lender is still done manually. The Leader checks in detail against the files in hard copy and completeness of other requirements. This makes leadership difficult in making decisions. This is the basis of the authors to conduct research with the title Application of the method of Multi Factor Evaluation Process on Decision Support System Licensor Feasibility determination (case study NSC Finance in the city of Lubuklinggau). With the construction of a system is expected to assist leaders in decision support supporters